Implementation of Character Education in Arabic Language Learning in Pesantren-Based University - As-Sa'idah, Rahmah; Mu'min, U Abdullah; Ismail, Moh. (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2025)
This study aims to describe the implementation of character education in Arabic language learning in pesantren-based universities, including curriculum, character education models, and psychological and sociological approaches used. This study employs a descriptive-qualitative approach with data collected through observation, in-depth interviews, and documentation studies at several pesantren-based universities in Indonesia. The results show that character education in Arabic language learning is integrated into competencies and objectives, emphasizing values like honesty, responsibility, discipline, and tawadhu’. The main model used is the Integrative-transformative approach, combining values with language learning through communicative and contextual methods. Psychologically, it focuses on value internalization through habituation and emotional bonds between teachers and students. Sociologically, it applies pesantren values, such as ukhuwah, musyawarah, and ta’dzim in class and extracurricular activities. To conclude, the successful implementation of character education in Arabic language learning in pesantren-based universities depends on the synergy between curriculum design, pedagogical approaches, and the social environment of pesantren that supports holistic character formation.